Adoção homoparental e diferença sexual - Érica Silva do Espírito Santo (2014)
The family and its transformations, as well as the rights conquered/achieved by the homosexuals/gays, brought to light/brought up a controversial question: the homoparentality. The possibility to acknowledge the homoparental family as a fully powered familiar formation and, from that, the adoption of children be granted is the core of this piece of work. Starting from this new reality, a question should be posed on what psychoanalysis could clarify on the topic. Thus, this piece of work consists of four steps: general considerations about adoption, family and homoparentality; some freudian texts readings that deal with sexual difference in order to clarify how classic psychoanalysis viewed the notion of such difference; introduction to Robert Stoller and gender identity constitutions, in a way so as to seek a counterpoint to classic psychoanalytical ideas; finally, study of empirical research on homoparentality and some considerations on homoparental adoption. The homoparental family has existed, the new aspect is the legal acknowledgment and the possibility of ensuring equivalent rights as the ones assured to heterosexual traditional family. The parents anatomic sex comes to light and the need to denaturalize the relation among parental functions and parents sex becomes evident in the sense that both motherly and fatherly functions can be fully performed regardless of either sex or gender from whom performs such functions. The homoparental family, as well as any other family, has no a priori success or failure guarantee. The adoptive homoparental family is a reality and it shows that such family possibility, although very recently acknowledged, is one of the avatars through which the family is introduced.